The post‐Palaeozoic fossil record of drilling predation on lingulide brachiopods. (8th November 2016) - Rojas, Alexis; Portell, Roger W.; Kowalewski, Michał
Abstract : Research on drilling predation, one of the most studied biological interactions in the fossil record, has been concentrated on prey with calcareous skeletons (e.g. molluscs, echinoids, rhynchonelliform brachiopods). Based on a compilation of literature sources and surveys of paleontological collections of the Florida Museum of Natural History and the National Museum of Natural History, we provide a tentative evaluation of the post‐Palaeozoic history of drilling predation on the organophosphatic brachiopods of the family Lingulidae. Despite temporal, geographical and methodological limitations of the data assembled here, the results indicate that lingulide brachiopods have been subject to drilling predation since at least the Eocene. Variation in drilling frequencies at the locality level suggests that lingulides may occasionally experience somewhat elevated predation pressures from drilling organisms. Overall, however, drilling predation on lingulide brachiopods has been infrequent in the Cenozoic and may have been absent in the Mesozoic. The Mesozoic‐to‐Cenozoic increase in drilling frequencies on lingulides is similar to the trends observed in other marine benthic invertebrates and consistent with the hypothesis that predation pressures increased through time in marine ecosystems.